Oral ulcers in children- a clinical narrative overview - Corinne Légeret; Raoul Furlano (BMC, 2021)
Abstract The prevalence of oral ulcers in children is reported to be 9%, however diagnosis of oral lesions can be challenging, being an unspecific symptom of several diseases. Differential diagnosis can range from classic infectious disease of childhood (e.g. herpangina, hand-foot-and-mouth-disease) over nutritional deficiencies, gastrointestinal disorders, inflammations (e.g. pemphigus vulgaris, lichen planus, mucous membrane pemphigoid) to side effects of medications (Stevens-Johnson Syndrome) or chronic dieseases (e.g. sarcoidosis, systemic Lupus erythematodes, familial Mediterrenean fever). Therefore, children with oral ulcers are treated by many different specialists such as dentists, family doctors, paediatricians, rheumatologists, haematologists, gastroenterologists and otorhinolaryngologists. A systematic literature search and a narrative literature review about the potential 48 diseases connected to oral ulcers were performed. According to the duration of symptoms and size of the lesions, a tabular overview was created to support the clinician in making a correct diagnosis, additionally different treatment options are presented.